FACTORS INFLUENCING EMPLOYEE GREEN BEHAVIOR AND EMPLOYEE GREEN ATTITUDE AMONG MUSLIMS IN INDONESIA - Kasmiarno, Kurnia Sari; Ekananda, Mahjus; Karmanto, Gina Destrianti (Journal of Environmental Science and Sustainable Development, 2025)
In a Muslim majority, developing country like Indonesia, religion shapes employees’ work ethic and professional behavior, embedding spiritual and cultural values into the workplace. Despite the increasing attention to pro-environmental behavior, previous studies have largely examined Green Human Resource Management (GHRM), religiosity, and environmental concern separately, often focusing on a single sector. This leaves employees from various occupational backgrounds underexplored. This study aims to examine the effects of Green Concern (GC), Green Motivation (M), GHRM, and Religiosity (REL) on Employee Green Behavior (EGB) and Employee Green Attitude (EGA) of Muslim employees in Indonesia. Data were collected through a quantitative survey of 300 Muslim employees across various occupational sectors and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings revealed that although GC, GHRM, and REL did not have a direct affect on EGB, they exerted a significant indirect effect when M was introduced as a mediating factor. The novelty of this study lies in establishing green motivation as a robust psychological mechanism explaining how GC, GHRM, and REL shape EGA and EGB among an underexplored population: employees across various occupational sectors. Furthermore, this study highlights the unique role of religiosity in influencing EGA and EGB among Muslim employees, differentiating it from prior research. Theoretically, this study advances the green behavior model by highlighting motivation as a key mediator. Practically, it suggest that organizations in Muslim-majority developing countries can enhance green behavior by implementing environmental training programs grounded in religious values and developing culturally sensitive reward systems designed to strengthen employee motivation commitment to sustainable practices.